2013
DOI: 10.1515/revneuro-2012-0084
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ozone exposure and associated injury mechanisms on the central nervous system

Abstract: Ozone (O3) is a component of photochemical smog, which is a major air pollutant and demonstrates properties that are harmful to health because of the toxic properties that are inherent to its powerful oxidizing capabilities. Environmental O3 exposure is associated with many symptoms related to respiratory disorders, which include loss of lung function, exacerbation of asthma, airway damage, and lung inflammation. The effects of O3 are not restricted to the respiratory system or function - adverse effects withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Oxidative stress is involved in many neurodegenerative diseases, in which the over-production of O 3 leads to both pathological and functional brain injuries [33]. Moreover, the environmental O 3 exposure is associated with a series of adverse effects within the central nervous system, such as decreased cognitive response, decrease in motor activity and headaches, disturbances in the sleep-wake cycle, cell degeneration, and neurochemical alterations [34]. Taken together, the paradoxical effects of O 3 may depend on its concentration: while high concentration of O 3 may impair nervous system, low level of O 3 may act as a protector.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is involved in many neurodegenerative diseases, in which the over-production of O 3 leads to both pathological and functional brain injuries [33]. Moreover, the environmental O 3 exposure is associated with a series of adverse effects within the central nervous system, such as decreased cognitive response, decrease in motor activity and headaches, disturbances in the sleep-wake cycle, cell degeneration, and neurochemical alterations [34]. Taken together, the paradoxical effects of O 3 may depend on its concentration: while high concentration of O 3 may impair nervous system, low level of O 3 may act as a protector.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal pattern of metabolic changes seen in the present study suggests that neuronal response might be stimulated prior to inflammation. A number of animal studies have shown that O 3 can induce neuroinflammation and activate catecholeminergic neurons likely through lung vagus afferents (Gackiere et al, 2011; Martínez-Lazcano et al, 2013). Activation of these central nervous system locations can stimulate sympathetic and HPA-mediated release of adrenal stress hormones in the systemic circulation, which can perturb metabolic functions involving glucose, lipids, and amino acids (Seematter et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pollutants may lead to an inflammatory reaction in the CNS or directly interfere with neuronal function that may affect sleep. 31…”
Section: Sleepmentioning
confidence: 99%